TRANSFORMASI KEPEMIMPINAN TEKNOKRATIS DI TIONGKOK ERA XI JINPING: IMPLIKASI TERHADAP KETAHANAN DAN PEMBANGUNAN INDONESIA - Victor Jacob Lucas Lapulalan; Ari Susiono; Tarsisius Susilo; Agus Soeprianto; Wahyu Tunggul Wiratama (Berajah Journal, 2025)
This study investigates the transformation of technocratic leadership in China under Xi Jinping and its implications for Indonesia’s resilience and development. Xi’s leadership, characterized by the fusion of technocratic competence, political centralization, and ideological consolidation, generates a paradox: while it enhances bureaucratic efficiency and strengthens China’s global influence, it also creates risks of economic dependency, geopolitical pressure, and erosion of democratic principles. For Indonesia, this transformation offers development opportunities through initiatives such as the Belt and Road, yet simultaneously poses challenges to maritime sovereignty and strategic autonomy. By employing a qualitative literature review of academic studies, policy documents, and relevant publications, this research contributes to the discourse on technocratic leadership by underscoring its cross-national consequences and provides practical insights for Indonesia to formulate adaptive responses through partnership diversification, institutional strengthening, and enhanced national resilience.